REVIEW: Coups, globalisation and Fiji’s reset ‘democracy’ paradigm - David Robie (Asia Pacific Network, 2018)
The General’s Goose: Fiji’s Tale of Contemporary Misadventure, by Robbie Robertson. Canberra: Australian National University. 2017. 366 pages. ISBN 9781760461270